2020
DOI: 10.1002/ejic.202000283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of “X” Ligands on the Photocatalytic Reduction of CO2 to CO with Re(pyridylNHC‐CF3)(CO)3X Complexes

Abstract: A series of five Re(pyNHC-aryl)(CO) 3 X complexes varying the "X" ligand where pyNHC is a pyridyl N-heterocyclic carbene have been synthesized and characterized through NMR, UV/Vis absorption spectroscopy, IR, mass spectrometry, time-correlated single photon counting, computational analysis, and cyclic voltammetry. The photocatalytic reduction of CO 2 to CO in the presence of a sacrificial electron donor with these complexes is evaluated using a simulated solar spectrum (AM [a] H.ing the effects of varying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The highest performing catalyst ( 2 ), the lowest performing catalyst ( 3 ), and the second highest performing catalyst ( 6 ) were analyzed computationally via density functional theory (DFT) with the M06‐2X [10] and PBE0 [10b,11] functionals and implicit MeCN solvation (see experimental section for a description of the computational approach and how the rhenium atom was treated). The M06‐2X and PBE0 functionals have been successfully employed elsewhere to characterize the structures and ligand dissociation energies of transition metal complexes [8a,10b] . In addition, time dependant DFT (TDDFT) computations with both functionals have been shown to reliably reproduce experimental UV‐Vis spectral features in combination with an appropriate implicit solvent model, specifically PBE0 with the closely related Re(bpy)(CO) 3 (Cl) complex and M06‐2X with polycyclic organic dyes [10b,12] .…”
Section: Resultsmentioning
confidence: 99%
“…The highest performing catalyst ( 2 ), the lowest performing catalyst ( 3 ), and the second highest performing catalyst ( 6 ) were analyzed computationally via density functional theory (DFT) with the M06‐2X [10] and PBE0 [10b,11] functionals and implicit MeCN solvation (see experimental section for a description of the computational approach and how the rhenium atom was treated). The M06‐2X and PBE0 functionals have been successfully employed elsewhere to characterize the structures and ligand dissociation energies of transition metal complexes [8a,10b] . In addition, time dependant DFT (TDDFT) computations with both functionals have been shown to reliably reproduce experimental UV‐Vis spectral features in combination with an appropriate implicit solvent model, specifically PBE0 with the closely related Re(bpy)(CO) 3 (Cl) complex and M06‐2X with polycyclic organic dyes [10b,12] .…”
Section: Resultsmentioning
confidence: 99%
“…In a later work, the axial ligand in 31 a was replaced by NCS, NCMe and P(OEt) 3 . [65] The catalytic performance of complexes bearing Br or NCMe was comparable, whereas the use of NCS and P(OEt) 3 significantly decreased the TON value reached by their metal complexes. Computational studies, together with excited-state lifetime measurements, revealed higher axial bond dissociation energy for the catalysts with less catalytic performance.…”
Section: Photoreduction Of Comentioning
confidence: 94%
“…Re complexes bearing inductively electron withdrawing substituents ( 31 a – 31 d ) exhibited higher TOF numbers compared to complex 35 bearing π‐electron withdrawing groups via resonance. In a later work, the axial ligand in 31 a was replaced by NCS, NCMe and P(OEt) 3 [65] . The catalytic performance of complexes bearing Br or NCMe was comparable, whereas the use of NCS and P(OEt) 3 significantly decreased the TON value reached by their metal complexes.…”
Section: Re‐nhc Complexes In Catalysismentioning
confidence: 99%
See 2 more Smart Citations